In vitro organ culture protocol for intact urogenital systems supporting gonadal differentiation - Sarah L. Whiteley; Clare E. Holleley; Arthur Georges (PLoS ONE, 2025)
Developing in vitro protocols for non-model species poses challenges, and yet are essential for advancing molecular biology studies. This is particularly true for sex determination research that relies on being able to functionally demonstrate the role of genes in determining sex and guiding the process of sex differentiation. Reptile species are attractive models for sex determination research as many species display thermolabile sex systems, allowing for exploration of gene-environment interactions. The first in vitro gonad culture technique for a turtle was published almost 35 years ago in 1990, but these techniques have seen limited use. This is likely because of challenges inherent to the system, where cultures need to be maintained for prolonged periods for gonadal differentiation to occur. All published techniques for long-term cultures involve removing the gonad from the surrounding mesonephros, which causes issues for proper testes development. Here we present the first protocol developed in the reptile model, Pogona vitticeps, that allows the long-term culture of the whole urogenital system supporting differentiation from biopotential gonads to ovaries or testes. Gross morphology is well maintained, and the gonad can be dissected from the mesonephros even after a culture period of up to 19 days. The cultured gonads display sex specific gene expression and morphology. This protocol will facilitate research in sex determination by providing an effective and low-cost alternative to existing protocols and expand capacity for functional manipulation studies in non-model species.